Effects of Omega-3 Fatty Acid Supplementation on Cognitive Functions and Neural Substrates: A Voxel-Based Morphometry Study in Aged Mice - Cutuli, Debora; Pagani, Marco; Caporali, Paola; Galbusera, Alberto; Laricchiuta, Daniela; Foti, Francesca; Neri, Cristina; Spalletta, Gianfranco; Caltagirone, Carlo; Petrosini, Laura; Gozzi, Alessandro (Frontiers in Aging Neuroscience, 2016)
Human and experimental studies have revealed putative neuroprotective and pro-cognitive effects of omega-3 polyunsaturated fatty acids (n-3 PUFA) in aging, evidencing positive correlations between peripheral n-3 PUFA levels and regional grey matter (GM) volume, as well as negative correlations between dietary n-3 PUFA levels and cognitive deficits. We recently showed that n-3 PUFA supplemented aged mice exhibit better hippocampal-dependent mnesic functions, along with enhanced cellular plasticity and reduced neurodegeneration, thus supporting a role of n-3 PUFA supplementation in preventing cognitive decline during aging. To corroborate these initial results and develop new evidence on the effects of n-3 PUFA supplementation on brain substrates at macro-scale level, here we expanded behavioral analyses to the emotional domain (anxiety and coping skills), and carried out a fine-grained regional GM volumetric mapping by using high-resolution MRI-based voxel-based morphometry. The behavioral effects of 8 week n-3 PUFA supplementation were measured on cognitive (discriminative, spatial and social) and emotional (anxiety and coping) abilities of aged (19 month-old at the onset of study) C57B6/J mice. n-3 PUFA supplemented mice showed better mnesic performances as well as increased active coping skills. Importantly, these effects were associated with enlarged regional hippocampal, retrosplenial and prefrontal GM volumes, and with increased post mortem n-3 PUFA brain levels. These findings indicate that increased dietary n-3 PUFA intake in normal aging can improve fronto-hippocampal GM structure and function, an effect present also when the supplementation starts at late age. Our data are consistent with a protective role of n-3 PUFA supplementation in counteracting cognitive decline, emotional dysfunctions and brain atrophy.